Pyrimidazole-Based Covalent Organic Frameworks: Integrating Functionality and Ultrastability via Isocyanide Chemistry - Liu, Jiao; Yang, Tong; Wang, Zhi-Peng; Wang, Peng-Lai; Feng, Jie; Ding, San-Yuan; Wang, Wei (Journal of the American Chemical Society, 2020)
Development of new chemistry to simultaneously meet the demands for topology, connectivity, and functionality is highly desired in the research area of covalent organic frameworks (COFs). We explore herein the isocyanide chemistry so as to establish a facile paradigm to integrate functionality and ultrastability in COFs. Using the representative Groebke–Blackburn–Bienaymé (GBB) reaction based on isocyanide chemistry, we are able to construct a series of pyrimidazole-based COFs in one step from isocyanide, aminopyridine, and aldehyde monomers. Diversified functionalities have been bottom-up integrated by the simple replacement of readily available 2-aminopyridine monomers. Meanwhile, the ubiquitous formation of fused imidazole rings within the frameworks has guaranteed their ultrastability. In view of the rich synthetic possibilities provided by isocyanide chemistry, we expect that this contribution opens up a new avenue toward the divergent construction of robust COFs for practical applications.